2000
DOI: 10.1152/jn.2000.83.2.998
|View full text |Cite
|
Sign up to set email alerts
|

Modifications of Seizure Susceptibility inDrosophila

Abstract: In a given population, certain individuals are much more likely to have seizures than others. This increase in seizure susceptibility can lead to spontaneous seizures, such as seen in idiopathic epilepsy, or to symptomatic seizures that occur after insults to the nervous system. Despite the frequency of these seizure disorders in the human population, the genetic and physiological basis for these defects remains unclear. The present study makes use of Drosophila as a potentially powerful model for understandin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
156
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(164 citation statements)
references
References 36 publications
7
156
1
Order By: Relevance
“…It was proposed that these mutants were associated with defects leading to increased membrane excitability (Benzer 1971;Ganetzky and Wu 1982). This idea is further supported by the reduced threshold for electrically induced seizures in these mutants (Kuebler and Tanouye 2000). Molecular identification of several of these mutants has suggested that they result from defects in mitochondrial metabolism (Royden et al 1987;Zhang et al 1999;Fergestad et al 2006a To examine the long-term effects of genetic perturbations conferring increased seizure susceptibility, we performed aging and histological analyses on these seizure mutants alone and in combination with ATPa mutations.…”
Section: /Kmentioning
confidence: 99%
“…It was proposed that these mutants were associated with defects leading to increased membrane excitability (Benzer 1971;Ganetzky and Wu 1982). This idea is further supported by the reduced threshold for electrically induced seizures in these mutants (Kuebler and Tanouye 2000). Molecular identification of several of these mutants has suggested that they result from defects in mitochondrial metabolism (Royden et al 1987;Zhang et al 1999;Fergestad et al 2006a To examine the long-term effects of genetic perturbations conferring increased seizure susceptibility, we performed aging and histological analyses on these seizure mutants alone and in combination with ATPa mutations.…”
Section: /Kmentioning
confidence: 99%
“…This phenotype has been associated with mutations in genes involved in neuronal function as well as mitochondrial integrity (33)(34)(35)(36)(37)(38). Two stress-sensitive mutants have been identified as nuclear-encoded mitochondrial genes: stress sensitive B (sesB), encoding the fly ortholog of the adenine nucleotide translocase (39), and technical knock-out (tko), encoding a subunit of the mitochondrial ribosome (40).…”
Section: Mutants Exhibit Partial Lethality and Reduced Viability-porinmentioning
confidence: 99%
“…Single-pulse stimuli (0.5 ms duration, 0.8 Hz) were used to drive the GF, and the GF-driven muscle potentials were recorded from the dorsal longitudinal muscle (DLM) using a tungsten recording electrode. Seizure-like spiking is observed in at least seven different muscle groups and over 30 muscle fibers in the thorax that reflect the HF firing of the innervating motoneurons (Kuebler and Tanouye 2000). Seizure-like activity was evoked by delivering short wave trains of HF electrical stimuli (0.5-ms pulses delivered at 200 Hz for 300 ms) to the fly's brain.…”
Section: Molecular Biologymentioning
confidence: 99%